The wide-aperture gamma-ray telescope TAIGA-HiSCORE in the Tunka Valley: Design, composition and commissioning - Gress O.; Astapov I.; Budnev N.; Bezyazeekov P.; Bogdanov A.; Boreyko V.; Bruckner M.; Chiavassa A.; Chvalaev O.; Dyachok A.; Gress T.; Epimakhov S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
The new TAIGA-HiSCORE non-imaging Cherenkov array aims to detect air showers induced by gamma rays above 30 TeV and to study cosmic rays above 100 TeV. TAIGA-HiSCORE is made of integrating air Cherenkov detector stations with a wide field of view (0.6 sr), placed at a distance of about 100 m. They cover an area of initially ∼0.25 km2 (prototype array), and of ∼5 km2 at the final phase of the experiment. Each station includes 4 PMTs with 20 or 25 cm diameter, equipped with light guides shaped as Winstone cones. We describe the design, specifications of the read-out, DAQ and control and monitoring systems of the array. The present 28 detector stations of the TAIGA-HiSCORE engineering setup are in operation since September 2015.